2017
DOI: 10.2209/tdcpublication.2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Implant-supported Oral Rehabilitation in Child with Ectodermal Dysplasia — 4-year Follow-up

Abstract: Ectodermal dysplasia (ED) is an anomaly determined by genetic factors that alter ectodermal structures such as skin, hair, nails, glands, and teeth. Children affected by this condition require extensive, comprehensive, and multidisciplinary treatment. An 8-yearold female patient visited the Dentistry Clinic of the Federal University of Santa Catarina with the chief complaint of multiple missing teeth. The mother reported that the patient had ED. Clinical and radiographic examination revealed the congenital abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The results showed that implant therapy is an effective treatment option for those with EDs 385 . In a case study, Triches et al 386 . mentioned that after 4 years of follow‐up, implants were a promising therapeutic option, restoring a child's masticatory, cosmetic and phonetic function.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that implant therapy is an effective treatment option for those with EDs 385 . In a case study, Triches et al 386 . mentioned that after 4 years of follow‐up, implants were a promising therapeutic option, restoring a child's masticatory, cosmetic and phonetic function.…”
Section: Discussionmentioning
confidence: 99%
“…For the restoration, overdentures were the most commonly used, either with ball attachments ( 14 , 15 ) or with a metal reinforcement structure ( 41 , 18 , 38 ). The teeth were usually made of acrylic-based resin, supported by mucosa, but retained by the implants.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal time of implant placement is defined by child's dental and skeletal maturity and is mostly indicated after the completion of jaw growth, to avoid potential trauma in the adjacent tooth germs and possible interference with the eruption of permanent teeth [ 6 , 24 , 25 ].. However, there are cases of ED with implant rehabilitation at 5-6 years of age [ 4 , 6 , 18 , 26 28 ]. It is an expensive treatment modality and a challenging process, especially for young children, and implants can only be placed under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%